IMPACT OF MEDICATION ADHERENCE ON THE SAFETY AND EFFICACY OF ANTIDIABETICS IN WORKING-AGE TYPE II DIABETES PATIENTS: A LONGITUDINAL STUDY - PRABHUDATTA MOHAPATRA; ASHRUMOCHAN DEBATA; DURGA MADHAB KAR; KARMAJEET RATH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of the study was to provide valuable insights into the importance of adherence in achieving optimal therapeutic outcomes, this study will analyze adherence trends, glycemic control, and the incidence of adverse drug reactions (ADRs) across time. Methods: In this longitudinal observational investigation, working individuals (30–60 years old) with Type 2 diabetes are evaluated for medication adherence, safety, and effectiveness of antidiabetic medications. With informed consent and ethical permission guaranteed, and evaluate data on ADRs, glycemic control, and treatment results. Result: A total of 460 patients are enrolled and split into adherent group (n=276) and non-adherent group (n=184) according to the proportion of days covered method. It was found that the non-adherent group had a slightly longer duration of diabetes (6.57±4.59 years) than the adherent group. Diabetes-related problems are directly impacted by medication adherence. More reductions in hemoglobin A1C (HbA1c) (7.22–6.54% vs. 7.59–6.97%), fasting glucose (181.35–148.68 mg/dL vs. 178.45–150.48 mg/dL), and postprandial glucose (213.41–187.14 mg/dL vs. 232.67–188.19 mg/dL) were observed in the adherent group than in the non-adherent group over a 12-month period. These results imply that a higher prevalence of certain ADRs, like hypoglycemia, is linked to non-adherence to diabetic treatments, and that experiencing ADRs may also be a contributing factor to medication non-adherence. Conclusions: In working-age patients with Type 2 diabetes, medication adherence significantly enhances the safety and effectiveness of antidiabetic medications, improving glucose control and lowering adverse drug responses.